2017
DOI: 10.1002/elps.201600491
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of isoxazolines with functionalized perphenylcarbamate cyclodextrin clicked chiral stationary phases in HPLC

Abstract: The enantioseparations of 12 isoxazoline racemates were explored with four perphenylcarbamate cyclodextrin (CD) clicked chiral stationary phases (CSPs) in high performance liquid chromatography (HPLC). The results demonstrated that the functionalities on phenylcarbamate moiety greatly determined the chiral separation ability of CD clicked CSPs. Among of them, per(3-chloro-4-methylphenylcarbamate) CD clicked CSP (CCC3M4-CSP) exhibited the best enantioseparation ability, affording 4ClPh-OPr with a chiral resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recently, the thiol‐ene reaction has attracted growing attention as it avoids the use of metal catalysts in Cu(I) catalytic 1,3‐dipolar cycloaddition, and it is used extensively for the development of chiral separation materials . Based on this art, our group developed a series cationic CD‐CSP by thiol‐ene click chemistry and confirmed its improved separation performance in LC . The CSP shows high enantioseparation ability to carboxylic aryl compounds, dansyl amino acids, isoxazolines, flavonoids, and so on in chiral HPLC.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, the thiol‐ene reaction has attracted growing attention as it avoids the use of metal catalysts in Cu(I) catalytic 1,3‐dipolar cycloaddition, and it is used extensively for the development of chiral separation materials . Based on this art, our group developed a series cationic CD‐CSP by thiol‐ene click chemistry and confirmed its improved separation performance in LC . The CSP shows high enantioseparation ability to carboxylic aryl compounds, dansyl amino acids, isoxazolines, flavonoids, and so on in chiral HPLC.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, the hydroxyl residues in the partially‐substituted β‐CD also enabled BACD‐HPS and MP‐CD‐HPS to be used under both normal and reversed‐phase conditions. Recently, it was reported that the enantioselectivity of the phenylcarbamate‐β‐CD‐based CSPs could be easily and flexibly adjusted when using chlorine and methyl functional groups to modify the phenylcarbamate moieties in the CSPs . Therefore, it is our interest to prepare a new type of partially‐substituted chlorine and methyl containing phenylcarbamate‐β‐CD‐bonded phase and to investigate its chromatographic performance in HPLC.…”
Section: Introductionmentioning
confidence: 99%